Analisis Kondisi Keuangan Pemerintah Kota Batam Tahun 2023-2024 - Dwi Hasmi Sulistiani; Victoria Kusumaningtyas Priyambodo (Jurnal Riset Mahasiswa Akuntansi, 2026)
Analysis of local government financial conditions plays a crucial role in providing a comprehensive overview of fiscal health, enabling early detection of budgetary imbalances, optimizing resource allocation, and enhancing accountability and regional development sustainability. This study aims to analyze the financial condition of the Batam City Government for the 2023-2024 period using a framework of six financial ratio dimensions: short-term solvency, budgetary solvency, long-term solvency, service solvency, financial flexibility, and financial independence. Employing a descriptive quantitative approach, this research utilizes secondary data from local government financial reports. The findings indicate that the overall financial condition of Batam City Government is relatively healthy and stable, with significant improvements in short-term liquidity, financial flexibility, and per capita service solvency, supported by the absence of long-term liabilities—despite pressures on budgetary solvency from rising personnel expenditures and declining financial independence due to weakening locally generated revenue (PAD) contributions. Overall, Batam City Government demonstrates high fiscal resilience against shocks, with substantial fiscal space for adaptation; however, optimizing PAD, controlling mandatory spending, and leveraging assets are essential to strengthen fiscal autonomy and ensure sustainable public service delivery amid population growth and strategic economic activities as a free trade zone.